In search of the “missing link" - Tomczyk, Jacek (Studia Ecologiae et Bioethicae, 2003)
Eighty years ago Raymond A. Dart wrote the papers about Australopithecus africanus and decided to classify it as a “missing link". The creature from Taung represented an ultra-simian and pre-human stock. Therefore, he proposed a new family Homo - simiadae. Nowadays, scientists on the occasion of this anniversary publish, many papers about this event. They want to remind discussion about Taung's child and in homage to Raymond A. Dart. Surprisingly, the discussion which took place in the thirties and forties was an exact repetition of the earlier debate about Trinil's fossil! In 1890/91 Dubois had found already ancient fossils in Java which classified as Pithecanthropidae - this new family was an evolutionary "bridge" between apes and man. However, despite the fact that anthropologists wanted to find a “missing link” they rejected those interpretations! Some of them thought that fossil form Taung and Trinil belonged to a true ape. Whereas the others believed that remains should have been classified as a hominid family. Those two debates indicate one scheme of thinking: 1. theoretical view of “missing link”; 2. empirical researching; 3. taxonomic debate about fossil; and 4. rejecting the idea of “missing link”.